Inflammatory and coagulation marker profiles in severe pediatric COVID-19 patients: a systematic review - Tartila Fathan; Antonius Hocky Pudjiadi; Nina Dwi Putri; Nindya Permata; Yosilia Nursakina (Indonesian Pediatric Society, 2022)
Background Children are susceptible to SARS-CoV-2 infection and often present mild manifestations. However, severe and critical cases have also been reported. The inflammation and coagulation marker profile pattern in these patients along with the white blood cell differential count in critical PICU cases with non-COVID-19 etiology is not entirely clear. Objective To evaluate the inflammation and coagulation profiles in children presenting with severe/critical SARS-CoV-2 infection. Methods A systematic search and review of scientific literature was conducted following the PRISMA guidelines using ProQuest, SCOPUS, EBSCOHost, ScienceDirect, Cochrane, EMBASE, and Pubmed databases. All relevant original studies until March 11, 2021, were included. The risk of bias was appraised using the Modified Newcastle Ottawa Scale and JBI Critical Appraisal Checklist tools. Results We identified 14 studies across 6 countries, including a total sample of 159 severe and critically ill pediatric COVID-19 patients. Most of the subjects showed normal leukocytes, but increased CRP, procalcitonin, ferritin, and IL-6. Studies on coagulation profiles showed normal thrombocytes, PT, aPTT, and inconsistent D-dimer results. Conclusion Inflammation and coagulation parameters in severe/critically ill children with COVID-19 are atypical. Several inflammatory markers were elevated, including CRP, ferritin, procalcitonin, and IL-6. However, the elevated marker values are still lower compared to non-COVID infection patients. Further investigation of the parameters need to be done in serial examination multicenter studies, which include control subjects.